Improving customer retention in the UAE - Nallaluthan, Kesavan; Al Falasi, Huda Mohammed (Ifma Publishing, 2023)
This article aims to explore the importance of customer retention in businesses in the UAE. The article provides evidence for a clear and distinct relationship between customer satisfaction, customer retention and the success of the company. The main focus is to enlist and evaluate the success of the techniques used to improve customer retention in the company. This includes building trust with the company, increasing empathy, creating loyalty programs, ensuring sufficient measures to combat customer dissatisfaction and being open to feedback from the customers. The article is based on primary and secondary research conducted by the author wherein journal articles, research papers and financial newsletters were consulted to conclude. The paper also focuses on how the tourism industry of the United Arab Emirates largely affects customer retention in the country. From the research conducted, it can be claimed that no one technique of customer retention is fully applicable in the country due to the unique circumstances under which it runs its businesses. However, a combination of techniques can prove to be successful for the country owing to the income of its tourists, patronage and referrals of its locals, the demand for tourism in the country and the shopping capital of the country